Application of Short Message Service (SMS) on Cinema Ticket Booking - Dhika Alfatah (Penerbit Jurnal Indonesia, 2022)
The objective applications Ticket Booking Theatres Short Message Service (SMS) to facilitate the work of Admin, in serving the customer. When booking tickets buyer has no need to come back and forth because just want to book tickets only. Booking cinema tickets. Data collection methods used in conducting this research is through primary data (interviews, observations) and secondary data (documents).From the results of the design and manufacturing applications can be concluded that the cinema ticketing system can be done via the Short Message Service (SMS).